2023
DOI: 10.1038/s41598-023-32638-w
|View full text |Cite
|
Sign up to set email alerts
|

Morphologies and composition changes in nonculprit subclinical atherosclerosis in diabetic versus nondiabetic patients with acute coronary syndrome who underwent long-term statin therapy

Abstract: Although patients are undergoing similar lipid-lowering therapy (LLT) with statins, the outcomes of coronary plaque in diabetic mellitus (DM) and non-DM patients are different. Clinical data of 239 patients in this observational study with acute coronary syndrome was from our previous randomized trial were analyzed at 3 years, and 114 of them underwent OCT detection at baseline and the 1-year follow-up were re-anlayzed by a novel artificial intelligence imaging software for nonculprit subclinical atheroscleros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…However, the natural outcome of NSA in patients with mild renal insufficiency (60�eGFR<90 mL/ (min×1.73 m 2 )) is not fully understood. Our study showed that even with a similar LLT, the TAVn of the NSA, which was detected by OCT and measured using novel OFR software that can measure plaque components automatically with a modern AI algorithm [10,24,25], increased significantly more in mild CKD than in non-CKD from baseline to the 1-year…”
Section: Plos Onementioning
confidence: 74%
See 4 more Smart Citations
“…However, the natural outcome of NSA in patients with mild renal insufficiency (60�eGFR<90 mL/ (min×1.73 m 2 )) is not fully understood. Our study showed that even with a similar LLT, the TAVn of the NSA, which was detected by OCT and measured using novel OFR software that can measure plaque components automatically with a modern AI algorithm [10,24,25], increased significantly more in mild CKD than in non-CKD from baseline to the 1-year…”
Section: Plos Onementioning
confidence: 74%
“…All OCT images were stored in DICOM format and analyzed offline with dedicated software (OFR, Pulse Medical Imaging Technology, Shanghai, Co., Ltd.) [24], which measured the quantitative planimetry of plaque characteristics by automatic border detection followed by manual correction, and each area of lipid, fibrous, calcium and macrophage components was measured frame by frame to determine the corresponding volumes in the measured segment PLOS ONE [24]. Finally, the quantitative indicators of each plaque component were recorded in accordance with previous studies, as follows [3,10,25]: external elastic membrane area (EEM area ) was defined as the cross-sectional area of the EEM, lumen area (Lumen area ) was defined as the cross-sectional area of the lumen, normalized total atheroma volume (TAVn) was calculated as S(EEM area -Lumen area )/number of frames of target segment×100, percent atheroma volume (PAV) was calculated as S(EEM area -Lumen area )/SEEM area ×100, lipid TAVn was defined as Slipid area /number of frames of target segment×100), lipid PAV was defined as Slipid area /SEE-M area ×100, fibrous TAVn was defined as Sfibrous area /number of frames of target seg-ment×100, fibrous PAV was defined as Sfibrous area /SEEM area ×100, calcium TAVn was defined as Scalcium area /number of frames of target segment×100, calcium PAV was defined as Scalcium area /SEEM area ×100, macrophage TAVn was defined as Smacrophage area /number of frames of target segment×100, and macrophage PAV was defined as Smacrophage area /SEE-M area ×100. The change in TAVn (ΔTAVn) was defined as the TAVn at the 1-year follow-up minus the baseline TAVn, which could be derived from lipid ΔTAVn, fibrous ΔTAVn, calcium ΔTAVn or macrophage ΔTAVn.…”
Section: Oct Image Acquisition and Analysismentioning
confidence: 99%
See 3 more Smart Citations